2021
DOI: 10.26480/faer.01.2021.41.45
|View full text |Cite
|
Sign up to set email alerts
|

Economic Impact of Agricultural Mechanization in Rice Farming in Shivasatakshi Municipality of Jhapa District, Nepal

Abstract: A study was conducted in Shivasatakshi municipality of Jhapa district to assess the economic impact of agricultural mechanization in rice farming in 2020. Altogether, 40 rice farmers were selected randomly and surveyed using a semi-structured interview schedule. Based on the use of machinery, farmers were categorized into mechanized and non-mechanized farmers. Cost and revenue were calculated among both categories. T-test was used to compare the mean cost and revenue between mechanized and non-mechanized rice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…It implies the financial viability of rice seed production in the study area. This result relates to the findings in the research on rice in Jhapa, where they found B: C ratio of 1.9 with mechanized rice farms (Khatiwada et al, 2021). But the average B: C ratio of Kailali contradicts the lower BCR 1.11 of rice research in Rautahat Nepal (Sapkota et al, 2021).…”
Section: Yield and Profitabilitysupporting
confidence: 79%
See 1 more Smart Citation
“…It implies the financial viability of rice seed production in the study area. This result relates to the findings in the research on rice in Jhapa, where they found B: C ratio of 1.9 with mechanized rice farms (Khatiwada et al, 2021). But the average B: C ratio of Kailali contradicts the lower BCR 1.11 of rice research in Rautahat Nepal (Sapkota et al, 2021).…”
Section: Yield and Profitabilitysupporting
confidence: 79%
“…But, 80% were from maleheaded households. This is linked with the study on rice in Jhapa wherein 85% of households were male-headed (Khatiwada et al, 2021). This denotes the community of rice farmers is male-dominated.…”
Section: Descriptive Analysismentioning
confidence: 91%
“…The challenges were initially included in the pre-structured schedule by reviewing the articles on problems faced by the paddy farmers in paddy production and marketing during the COVID-19 regime. The challenges faced by the paddy farmers in paddy production and marketing during the COVID-19 regime were as follows: Lack of accessibility to the market, nonavailability of inputs, high input cost, nonavailability of farm labour, high wage rate of labour, high transportation costs, non-availability of the required information on price/prices in other markets, lack of warehousing facility, nonavailability of packaging material, No financial assistance, lack of storage facilities, lack of adequate extension support, middlemen malpractices and delay in payments after selling the produce [8][9][10][11].…”
Section: Methods Of Data Analysismentioning
confidence: 99%
“…All the inquiries such as increase in production, increase in income, reduction in cultivation costs, loan accessibility, increase in purchasing power, and increased investment have set down to be significant at 1% level of significance clearly exhibited the effect of farm machineries in the paddy cultivation and economical benefit to the farmers. Hence it was observed that there was positive impact of farm mechanization on income [10,11,12]. Increased yield, reduced cost of cultivation merits of mechanization [13,14,15].…”
Section: Social Impactmentioning
confidence: 99%